SHELFAL PALEO-RIVER VALLEYS, SLOPE CANYONS, DEEPWATER FANS & MASS TRANSPORT DEPOSITS AND THEIR INFLUENCE ON HYDROCARBON MIGRATION TO THE NORTH-WESTERN SHELF OF THE BLACK SEA - TYSHCHENKO, Andrii; KITCHKA, Oleksandr; VYZHVA, Andrii (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. The tectonic evolution and structural constructions of the East European Platform offshore convergence zone, the PreDobrogea foredeep on the Scythian Plate and the overlaid Meso-Cenozoic Black Sea Basin are particularly complicated. The presented research of this convergence zone spatially corresponds to the shallow inner part of the Black Sea northwestern shelf.Methods. A thematic geological interpretation of regional 2D CDP seismic data was performed, including 47 profiles with a total length of almost 10,000 km acquired for Naftogaz of Ukraine in 2005 and re-processed using the true amplitude reconstruction method. These structural constructions were complemented by the interpretation of slightly denser 2D CDP seismic data acquired by Western Geophysical in 1994, although the latter used different acquisition parameters and processing techniques.Results. For the first time based on the results of comprehensive studies, a large-scale system of deep-sea mass-transfer complexes of Neogene-Quaternary age was mapped within the Ukrainian northwestern part of the Black Sea and adjacent offshore. Based on the thematic interpretation, it was found that the deep-sea submarine mass transfer complex system in its plane slip bottom part forms a multi-level screen system on the way of upward hydrocarbon migration. A detailed geological interpretation of seismic and deep drilling data allowed us to identify a drainage network that combines reservoir turbidites and distal alluvial fans, as well as incised valley filling complex of the continental paleoslope and inner shelf buried river paleodunes.Conclusions. The system of marginal high-amplitude normal faults at paleo-shelf hinge and erosion surfaces facilitates migration of hydrocarbons form lower to higher stratigraphic levels of deepwater domain and their permeation into adjusted paleo-shelf terrace through the contact with older reservoir in Upper Cretaceous, Paleocene and Eocene strata that is quite important issue for planning of exploration activity for oil and gas in this region.
Keywords: mass transport deposits (MTDs); Northwestern Black Sea; exploration; sequences; interpretation; hydrocarbon migration